MENENTUKAN METODE PERAMALAN YANG TEPAT - Ria Satyarini (Center for Economic Studies Universitas Katolik Parahyangan, 2007)
Forecasting methods are basic tools that we have to know to make assumptions for planing or decision making. There are a lot of forecasting method, and as a decision maker we have to choose the right model for our type of data. Choosing the right model of forecasting is not difficult if we know the pattern of the-data and the requirements of the method. This paper described how we could choose the right forecasting. Methods for the data, and analyze which forecasting method is the best among the alternatives.Keyword: Forecasting, forecasting methods, and stationary test